THE ROLE OF BUSINESS IN FULFILLING CHILDREN’S RIGHTS AND PREVENTING THE MISUSE OF FINANCIAL INSTITUTIONS FOR THE SEXUAL EXPLOITATION OF CHIDREN - Fransiska Novita Eleanora; Adhalia Septia Saputri (Adisam Publisher, 2025)
Children are the next generation of the nation who will continue their struggles and ideals, so they must always be given attention and supervision and, most importantly, their rights are protected. Child protection is an effort to ensure continuity in ensuring the continuity of children's rights to live, grow, develop and participate optimally in accordance with human dignity, as well as receive protection from violence and discrimination. The business world can play a role in providing full protection and responsibility for respecting children's rights regarding their human rights by paying attention to the code of ethics for child protection and decent work, emergency situations and the best interests of children and can prevent acts of sexual exploitation of children, including criminal acts of pornography and human trafficking (extra ordinary crimes). In this way, the business world and financial providing institutions must always coordinate and cooperate in monitoring transactions carried out for human trafficking, and one form of preventing sexual exploitation of children is by building a high sense of legal awareness among the parties involved so that this does not happen. actions that are detrimental to children's human rights.